Nano Online 2016
DOI: 10.1515/nano.0034.00048
|View full text |Cite
|
Sign up to set email alerts
|

Metal nanoantimicrobials for textile applications

Abstract: Research on the nanomaterials containing one or more transition metals is growing tremendously, thanks to the large number of preparation processes available and to the novel applications that can be envisaged in several fields. This review presents an overview of the selected studies in the field of antimicrobial textiles, employing bioactive nanophases of elements/compounds such as silver, copper, or zinc oxide. In addition, the history of use of these antimicrobials and their mechanism of action are shortly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 150 publications
0
10
0
Order By: Relevance
“…The antibacterial activity of the Ag-titania fabric composite against Escherichia coli (gram-negative) and Staphylococcus aureus (gram-positive) cultures was also reviewed. EI-Rafie reported that as low as 54 ppm nanosilver for cotton textile was sufficient for effective antimicrobial finishing [11]. The efficiency of the antibacterial finish on such textile was 97 and 91 % for Staphylococcus aureus and Escherichia coli, respectively.…”
Section: Health and Hygiene Textiles Using Nano And Bio-materialsmentioning
confidence: 99%
“…The antibacterial activity of the Ag-titania fabric composite against Escherichia coli (gram-negative) and Staphylococcus aureus (gram-positive) cultures was also reviewed. EI-Rafie reported that as low as 54 ppm nanosilver for cotton textile was sufficient for effective antimicrobial finishing [11]. The efficiency of the antibacterial finish on such textile was 97 and 91 % for Staphylococcus aureus and Escherichia coli, respectively.…”
Section: Health and Hygiene Textiles Using Nano And Bio-materialsmentioning
confidence: 99%
“…Smart textiles are one of the most promising application fields where antimicrobial nanostructures, frequently referred as nano‐antimicrobials , can be proficiently used as high performing nano‐reservoirs, providing a controlled release of bioactive non‐conventional inorganic species . The development of new antimicrobial fabrics is receiving great attention, because of the growing need for optimal hygienic conditions and specific devices that can help preventing the spread of many pandemic diseases .…”
Section: Introductionmentioning
confidence: 99%
“…The development of new antimicrobial fabrics is receiving great attention, because of the growing need for optimal hygienic conditions and specific devices that can help preventing the spread of many pandemic diseases . Various types of antimicrobial agents are generally used to limit or eliminate phenomena of textile degradation (color loss or fibers deterioration), unpleasant odors, and especially the growth of pathogenic microorganisms . In general, when let in contact with the human body, both natural and synthetic fibers can constitute an ideal environment for microbial growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations